Principal Managerial Leadership in Managing Professional Learning Communities in Elementary Schools - Tumiyati, Tumiyati; Nurkolis, Nurkolis; Ariyanto, Lilik (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
This study examines the critical role of principals in managing Professional Learning Communities (PLCs) to enhance teacher professional development and improve the quality of education in elementary schools. This study used a qualitative case study approach, with data collected through interviews, observation, and documentation. The results indicate that principals play a dynamic managerial role in the success of PLCs through comprehensive management functions, including planning, organizing, mobilizing, and controlling (POAC). Specifically, principals conduct in-depth needs analyses based on educational data, strategically plan and organize resources, and actively engage teachers in collaborative activities that foster a culture of participatory learning. Furthermore, regular reflection and data-driven evaluation ensure that the learning community remains aligned with school goals, leading to measurable improvements in teaching practices and student learning outcomes. This study highlights the importance of principal leadership in overcoming challenges such as resistance to change and limited integration of digital platforms. This study contributes to the literature by emphasizing the importance of principals’ managerial skills in effectively managing PLCs to achieve sustainable education reform. Practical implications suggest that principals need to focus on data-driven planning, resource optimization, and ongoing teacher engagement to strengthen PLCs in schools.